Enhancing Critical Thinking and Curiosity in Early Childhood Through Inquiry-Based Science Learning - Agustini, Rini; Meilanie, R. Sri Martini; Pujiastuti, Sri Indah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Early childhood is a critical period for cognitive, social, and emotional development, making it essential to foster critical thinking and curiosity in educational settings. This study explores the implementation of inquiry-based science learning for children aged 5-6 years within the Merdeka Curriculum framework to enhance these key developmental skills. Using a Research and Development (R&D) approach, the study designed, implemented, and evaluated inquiry-based science modules. Data were collected through a combination of qualitative and quantitative methods, including observations, interviews, and pre- and post-tests. The findings revealed that inquiry-based learning significantly improved children’s critical thinking, curiosity, and understanding of scientific concepts, with pre-test scores improving from 46.29% to 80.57% in small group trials and from 48.38% to 80.76% in large group trials. While the approach increased student engagement and curiosity, teachers faced challenges in managing inquiry-based classrooms, indicating the need for further professional development. The study concludes that inquiry-based science learning aligns with the goals of the Merdeka Curriculum, promoting active learning and cognitive growth in early childhood education. Further support for teachers is recommended to ensure effective implementation and classroom management